Analysis Of Factors Affecting the Gender Development Index of Indonesia in 2023 - Isma Nada; Dedy Yuliawan (International Journal of Economics, Management and Accounting (IJEMA), 2024)
Human quality, whether male or female, can be said to be high if they have better life choices such as high education and skills, high levels of health and high income. Although efforts have been made to improve the role and quality of women in development, the gender gap still exists in many areas compared to men. Using the human development index (women), women's income contribution in the family, and the percentage of women as professionals as independent variables and using the cross-section method in conducting regression, it is known that all independent variables have a positive and significant effect on the Gender Development Index in 34 Indonesian provinces.